Distribution of hornbills in western Sarawak and the way forward for their conservation in Sarawak - Pengiran, P.; Kheng, S.L.; Tisen, O.B.; Tuen, A.A.; Mohd Azlan, Jayasilan (Sarawak Museum, 2018)
There are eight species of hornbills in Borneo. However, little is known on their distribution and ecology in western Sarawak. Their large size requires habitats that consist of large forest patch with large fruiting trees for feeding and nesting. They have an important ecological niche as seed dispersers describes the distribution of hornbills in Totally Protected Areas (TPA) within western Sarawak based on data collected by Sarawak Forestry Corporation from 2013 2016. We discuss the hornbill species distribution and the species area relationship within western Sarawak. The Rhinoceros Hornbill (Buceros rhinoceros) recorded the highest occupancy value (psi) and probability of detection (p), followed by the Black Hornbill (Anthracoceros malayanus) and the Bushy-crested Hornbills (Anorrhinus galeritus). The Helmeted Hornbills (Rhinoplax vigil) appears to occur in fewer TPA within western Sarawak. A long-term conservation plan is required to ensure the sustainability of the hornbill population through extending protected areas and connecting forest patches. In light of this, the research and conservation needs for these species in Sarawak are highlighted to ensure their long-term survival in the wild.